Plasminogen deficiency does not prevent sodium retention in a genetic mouse model of experimental nephrotic syndrome - Xiao, Mengyun; Bohnert, Bernhard N.; Aypek, Hande; Kretz, Oliver; Grahammer, Florian; Aukschun, Ute; Woern, Matthias; Janessa, Andrea; Essigke, Daniel; Daniel, Christoph; Amann, Kerstin Ute; Huber, Tobias B.; et al. (Acta Physiologica, 2020)
Aim: Sodium retention is the hallmark of nephrotic syndrome (NS) and mediated by the proteolytic activation of the epithelial sodium channel (ENaC) by aberrantly filtered serine proteases. Plasmin is highly abundant in nephrotic urine and has been proposed to be the principal serine protease responsible for ENaC activation in NS. However, a proof of the essential role of plasmin in experimental NS is lacking. Methods: We used a genetic mouse model of NS based on an inducible podocin knockout (Bl6-Nphs2tm3.1Antc*Tg(Nphs1-rtTA*3G)8Jhm*Tg(tetO-cre)1Jaw or nphs2Δipod). These mice were crossed with plasminogen deficient mice (Bl6-Plgtm1Jld or plg−/−) to generate double knockout mice (nphs2Δipod*plg−/−). NS was induced after oral doxycycline treatment for 14 days and mice were followed for subsequent 14 days. Results: Uninduced nphs2Δipod*plg−/− mice had normal kidney function and sodium handling. After induction, proteinuria increased similarly in both nphs2Δipod*plg+/+ and nphs2Δipod*plg−/− mice. Western blot revealed the urinary excretion of plasminogen and plasmin in nphs2Δipod*plg+/+ mice which were absent in nphs2Δipod*plg−/− mice. After the onset of proteinuria, amiloride-sensitive natriuresis was increased compared to the uninduced state in both genotypes. Subsequently, urinary sodium excretion dropped in both genotypes leading to an increase in body weight and development of ascites. Treatment with the serine protease inhibitor aprotinin prevented sodium retention in both genotypes. Conclusions: This study shows that mice lacking urinary plasminogen are not protected from ENaC-mediated sodium retention in experimental NS. This points to an essential role of other urinary serine proteases in the absence of plasminogen.
CRIS-Team Scopus Importer:2020-08-07
Keywords: epithelial sodium channel; nephrotic syndrome; plasminogen; proteasuria; sodium retention